Exploring radiographic patterns of the cervical spine, including zygapophyseal joints, in axial spondyloarthritis - Joan Miquel Nolla; Diego Benavent; Xavier Juanola; Xabier Michelena; Laura Berbel-Arcobé; José Antonio Narváez (RMD Open)
Introduction The assessment of the cervical spine (CS) in axial spondyloarthritis (axSpA) and its radiographic characteristics, including the zygapophyseal joints (ZJ), may be helpful for an accurate diagnosis, establishing a prognosis and enhancing treatment decisions.Objectives To describe the prevalence and characteristics of CS involvement in patients with axSpA and perform a comparison between groups according to cervical radiographic damage.Methods Patients who fulfilled the Assessment of SpondyloArthritis International Society classification criteria were included from January 2011 to January 2021. Sociodemographic, clinical, radiographic and treatment variables were gathered. Patients were categorised into ‘CS group’ (Bath Ankylosing Spondylitis Radiology Index ≥2 or De Vlam score ≥3 for ZJ) and ‘no CS group’ as controls. ZJ fusion and interobserver reliability in ZJ scoring were analysed.Results A total of 340 patients were included, 244 (71.7%) men, with mean age 57±15 years. CS involvement was observed in 181 (53.2%) patients. Patients in the CS group, as compared with no CS group, were predominantly men, older, had a higher body mass index, higher prevalence of smoking, showed higher disease activity, worse functionality and mobility, as well as more structural damage. Sixty-nine patients with CS involvement had ZJ fusion at some level. These patients showed worse mobility and more radiographic damage. Overall, ZJ involvement was observed in 99 patients (29.1%), 20 of whom did not present with vertebral body involvement.Conclusion Radiographic evaluation of CS is relevant in patients with axSpA and should be assessed routinely. Evaluation of the ZJ is particularly significant, as it is related to higher disease activity and worse function.